Retinoic acid-induced 2 deficiency impairs genomic stability in breast cancer - Lena Boettcher; Sarah Greimeier; Kerstin Borgmann; Shabbir S. Mughal; Bernhard Ellinger; Kai Bartkowiak; Bernd Zobiak; Antonio V. Failla; Pascal Steffen; Ellen Claus; Katharina Besler; Christopher Buccitelli; et al. (Breast Cancer Research)
Abstract Background Genome instability is a fundamental feature and hallmark of cancer, associated with aggressiveness, drug resistance and poor prognosis. RAI2 was initially identified as a novel metastasis suppressor protein specifically associated with the presence of disseminated tumour cells in the bone marrow of breast cancer patients, but its molecular function is largely unknown. Methods We analysed the consequences of RAI2 depletion on gene expression and genomic stability in luminal breast cancer cell lines, performed cytotoxicity profiling using a library of pharmacologically active compounds, and characterized a potential function of the RAI2 protein in the DNA damage response. We performed in silico validation in different breast cancer datasets. Results Analysis of clinical samples revealed that in primary breast tumours, low RAI2 gene expression is significantly associated with genomically unstable tumours and poor prognosis. RAI2 depletion in breast cancer cell lines resulted in loss of mitotic fidelity characterized by prolonged mitosis with increased chromosome segregation errors and micronuclei formation. Drug screening revealed increased sensitivity of RAI2-depleted breast cancer cells to topoisomerase I and Aurora A inhibitors. We also found that genotoxic stress induces the RAI2 protein, which has an affinity for and colocalises with poly-(ADP-ribose). We validated the association of RAI2 gene expression with DNA repair capacity in clinical samples. Conclusions Our findings support, for the first time, a functional role of RAI2 in the maintenance of genomic stability. Understanding the underlying the molecular mechanism could help to improve patient diagnosis and treatment.